First report of the spider genus Symphytognatha from Asia (Araneae, Symphytognathidae) - Lin, Yucheng (Zootaxa, 2019)
Symphytognatha Hickman, 1931 was originally erected by Hickman (1931) as the type genus of the spider family Symphytognathidae. Forster and Platnick (1977) reviewed the family and proposed a diagnosis for Symphytognatha: almost completely fused chelicerae with a visible suture line and multidentate superior claws on legs I and II (but not on legs III and IV). Currently this genus contains 14 species (World Spider Catalog 2019), mainly widespread in South Africa (Griswold 1987), Oceania (Hickman 1931, Forster & Platnick 1977, Platnick 1979, Harvey 1992, 2001), and Central and South America (Balogh & Loksa 1968, Forster & Platnick 1977, Georgescu 1988, Brescovit, Álvares & Lopes 2004, Dupérré & Tapia 2017).